Two novel cases of autosomal translocations in the horse: Warmblood family segregating t(4;30) and a cloned arabian with a de novo t(12;25) - Ghosh, Sharmila (2020)
We report 2 novel autosomal translocations in the horse. In Case 1, a breeding stallion with a balanced t(4p;30) had produced normal foals and those with congenital abnormalities. Of his 9 phenotypically normal offspring, 4 had normal karyotypes, 4 had balanced t(4p;30), and 1 carried an unbalanced translocation with tertiary trisomy of 4p. We argue that unbalanced forms of t(4p;30) are more tolerated and result in viable congenital abnormalities, without causing embryonic death like all other known equine autosomal translocations. In Case 2, two stallions produced by somatic cell nuclear transfer from the same donor were karyotyped because of fertility issues. A balanced translocation t(12q;25) was found in one, but not in the other clone. The findings underscore the importance of routine cytogenetic screening of breeding animals and animals produced by assisted reproductive technologies. These cases will contribute to molecular studies of translocation breakpoints and their genetic consequences in the horse.